2010
DOI: 10.1002/pits.20502
|View full text |Cite
|
Sign up to set email alerts
|

Empowering Latino families: Effects of a culturally responsive intervention for low‐income immigrant Latino parents on children's behaviors and parental stress

Abstract: This randomized, controlled study examined the effectiveness of Child Parent Relationship Therapy (CPRT) in school settings with 48 low-income Latino immigrant parents whose children were identiÞed with behavioral concerns. Results from a 2 (group) × 2 (measures) split plot analysis of variance indicated that parents who participated in 11 weeks of CPRT reported statistically signiÞcant decreases (p < .001) in child behavior problems and parent -child relationship stress. Large treatment effects were demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 44 publications
2
79
0
2
Order By: Relevance
“…It is known that the socioeconomic status of immigrant families has a great impact on children's difficulties (Duncan et al 1994;Bradley and Corwyn 2002). CLD students in low-income families are reported to exhibit learning and behavioral problems more frequently (Ceballos and Bratton 2010). Parents' educational background and involvement in child rearing also have an impact on the children's academic achievement and behavioral problems (Bradley et al 2001;Suárez-Orozco et al 2009;Villiger et al 2014).…”
Section: Home Environment Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…It is known that the socioeconomic status of immigrant families has a great impact on children's difficulties (Duncan et al 1994;Bradley and Corwyn 2002). CLD students in low-income families are reported to exhibit learning and behavioral problems more frequently (Ceballos and Bratton 2010). Parents' educational background and involvement in child rearing also have an impact on the children's academic achievement and behavioral problems (Bradley et al 2001;Suárez-Orozco et al 2009;Villiger et al 2014).…”
Section: Home Environment Perspectivementioning
confidence: 99%
“…Reports on Japanese-Brazilian populations in Japan note that many fathers are engaged in heavy manual labor and have relatively low levels of education (Liu et al 2014) suggesting it may be difficult for them to be actively involved with their children's education. Research has found that parents' stressors are associated with poverty, and there is an emphasis on the importance of support and intervention for families (Ceballos and Bratton 2010;Sung 2014), which may play an important role in providing students with psychological stability and in improving their behavior.…”
Section: Factors Affecting Behavioral Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ceballos and Bratton (2010) found significant decreases in child behavior problems for 48 children of Latino immigrants using CPRT referred in the school setting. Kale and Landreth (1999) found changes in parental acceptance and parental stress, but no significant difference in behavior for children with learning difficulties.…”
Section: Efficacy Of Filial Therapymentioning
confidence: 85%
“…Differences in effect sizes for the current study may be accounted for by the difficulty in treating children with attachment disorders, the attrition rates, and conducting research in a CMHC. Ceballos and Bratton (2010) found CPRT resulted in significant decreases in child behavior problems for 48 Latino immigrant children; however, this intervention was directed at teachers in the school setting. Garza (2005) did not incorporate caregivers in the intervention, but found a decrease in externalizing behaviors.…”
Section: Findings Related To the Literaturementioning
confidence: 94%